Assessment of Scientific and Technological Potential of Research Organizations - A. S. Kulagin; L. P. Kleeva (Ekonomika Nauki, 2023)
The article examines the problem of activating the scientific and technological development of the Russian Federation based on the implementation of its own scientific priorities. This problem has two aspects: formation of such priorities and ensuring their most productive and effective implementation, including by identifying potentially most effective actors of scientific and technological activity. The aim of the work is to form, based on the existing experience and verbal analysis, an approach to creating a list of scientific priorities in the Russian Federation and ensuring their most productive and effective implementation, including by identifying subjects of scientific and technological activity that have the greatest potential in a particular field.To determine the scientific and technical potential of potential participants in scientific and technological projects, it is proposed to consider three elements: continuity of research and development, available material and technical base, and the qualification level of personnel. An expert assessment is proposed to be carried out for each of these three directions. These assessments can be supplemented by the results of monitoring the effectiveness of scientific and technological activities.